2014
DOI: 10.1099/mic.0.069948-0
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of endothelial cells and arthritogenic potential of endocarditis-associated Corynebacterium diphtheriae

Abstract: Although infection by Corynebacterium diphtheriae is a model of extracellular mucosal pathogenesis, different clones have been also associated with invasive infections such as sepsis, endocarditis, septic arthritis and osteomyelitis. The mechanisms that promote C. diphtheriae infection and haematogenic dissemination need further investigation. In this study we evaluated the association and invasion mechanisms with human umbilical vein endothelial cells (HUVECs) and experimental arthritis in mice of endocarditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…Non-toxigenic C. diphtheriae strains by definition do not contain the tox carrying β-corynephage, but do vary in their abilities to adhere to host cells, intracellular viability and their ability to stimulate cytokine production by the host immune system which may influence the severity of the disease due to infection (Bertuccini et al, 2004;Hirata et al, 2002;Peixoto et al, 2014;Puliti et al, 2006). These strains differ from each other in the presence and organisation of different pilus gene clusters, spaA, spaD and spaH (Sangal et al, 2015;Trost et al, 2012).…”
Section: Variation In Pathogenicity and Invasive Strainsmentioning
confidence: 96%
“…Non-toxigenic C. diphtheriae strains by definition do not contain the tox carrying β-corynephage, but do vary in their abilities to adhere to host cells, intracellular viability and their ability to stimulate cytokine production by the host immune system which may influence the severity of the disease due to infection (Bertuccini et al, 2004;Hirata et al, 2002;Peixoto et al, 2014;Puliti et al, 2006). These strains differ from each other in the presence and organisation of different pilus gene clusters, spaA, spaD and spaH (Sangal et al, 2015;Trost et al, 2012).…”
Section: Variation In Pathogenicity and Invasive Strainsmentioning
confidence: 96%
“…An infection by a non-toxigenic C. diphtheriae strain may vary from a localized respiratory tract infection to more invasive endocarditis, septic arthritis and osteomyelitis [ 8 12 ]. The severity of the disease is dependent on the ability of C. diphtheriae strains to adhere to host cells, intracellular viability and the induction of cytokine production by the host immune system [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of C. diphtheriae by TLR2 (1) leads on the one hand to upregulation of the C-type lectin receptor Mincle (2) and on the other hand, to phagocytosis of the bacteria (3), resulting in phagosome-lysosome fusion, which is somehow delayed by C. diphtheriae (4). Furthermore, binding of C. diphtheriae to Mincle (5) triggers the production of pro-inflammatory cytokines (6), which was confirmed by reduced cytokine production in Clec4e −/cells (7). Additionally, in Myd88deficient cells the cytokine production as well as the uptake of the bacteria was completely blocked (8).…”
Section: Discussionmentioning
confidence: 84%
“…The production of IL-6 and G-CSF leads to receptor-mediated activation of the JAK2/STAT3 (Janus Kinase/signal transducer and activator transcription) pathway [26,27], which subsequently leads to the induction of cell survival signals by producing increased levels of the anti-apoptotic proteins Bcl-2 and Bcl-X L. In case of C. diphtheriae, the knowledge about molecular signaling upon infection of macrophages is scarce. A number of studies showed that C. diphtheriae, once considered as strict extracellular pathogen, is able to cause severe invasive diseases, such as osteomyelitis, septic arthritis and endocarditis [6][7][8], which enhances the compelling need to focus on the infection mechanism of C. diphtheriae. In the study presented here, seven nontoxigenic C. diphtheriae isolates as well as two toxinproducing strains were characterized with regard to their interaction with BMM and human THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation